OPTIMASI RASIO C/N PADA PRODUKSI BIOMASSA DAN ASTAKSANTIN DALAM SPIROGYRA SP. MENGGUNAKAN PEMODELAN KINETIKA DAN RESPONSE SURFACE METHODOLOGY - Putu Ikrar Satyadharma, I
Astaxanthin is a carotenoid compound with antioxidant activity higher than other antioxidant compounds. Astaxanthin is produced by a variety of autotrophic organisme, such as the freshwater green algae Spirogyra sp., however unfortunately in limited quantity. Astaxanthin production in green algae is suspected to increase with addition of inorganic and organic carbon sources into the cultivation media. In this study, the effect of organic carbon (CH3COOH) addition with C/N parameters on growth and astaxanthin production in Spirogyra sp. culture, as well as the optimal C/N ratio was explored. Spirogyra sp. was cultivated in 25% BG-11 medium with variation of CH3COOH addition was adjusted to C/N ratio of 1:1; 2:1; 3:1; 4:1; and 5:1. Each variation was repeated three times. The nitrogen source (NaNO3) was derived from the composition of the standard 25% BG-11 medium. Cultivation was carried out for 15 days with destructive harvesting every 3 days. Extract of Spirogyra sp. dry biomass was analyzed for astaxanthin using High Performance Liquid Chromatogtraphy. Logistic and Haldane model was used to estimate the growth kinetic parameters of biomass. Substrate NaNO3 consumption kinetics parameter was also estimated using the Haldane model. Luedeking-Piret equation was used to estimate astaxanthin production kinetics parameters. Significance of data on variation was analyzed using ANOVA test and Tukey post-hoc test. Correlation was also analyzed using Pearson Correlation Coefficient parameter. Results showed an increase in the yield of biomass with the addition of CH3COOH, with the highest maximum biomass of 373.4 ? 61.2 mg/L was obtained at 1:1 C/N ratio on day 15. CH3COOH addition was also found to increase astaxanthin production with the highest astaxanthin level of 70.1 ? 41.2 ?g/gdry weight was obtained at 1:1 C/N ratio cultivation on day 9. According to response surface methodolgy (RSM) analysis using thin plate spline interpolation, the highest yield of astaxanthin was predicted to be achieved on carbon concentration range of 46,5 - 78,3 mg/L or equal to C/N ratio of 0.74:1 – 1,25:1; in a 8.5-9.7 cultivation day period. According to astaxanthin productivity estimation, the highest productivity of 3.31 ?g L-1 day-1 was obtained at C/N ratio of 4:1.